Applying Quizziz Application to Improve the Reading Comprehension in Narrative Text of 10th Grade Students - Nur Hismarliza S.R., Zachwa; Fathor Rasyid (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
Reading skills is skill that can explore the vast world of knowledge and information. One method to develop students' reading comprehension that can be taken is to use media-based learning online application. The purpose of this study was to analyze the effectiveness of the Quizizz application in teaching English language to students. The writer employed a quasi-experimental design, and the sample was taken from two classes, X IPA2 and X IPA 4. The researcher reported the students' pre-test and post-test scores for the experimental and control classes in this section. The researcher used the ANCOVA component of the SPSS 25 software to analyze the data. The findings show that the significant value of the class is 0.646 which is higher than 0.05. Therefore, the null hypothesis is accepted, and the alternative hypothesis is rejected based on the result above. It means that students who are taught by Quizziz Application doesn’t have better achievement than students who are taught using Textbook. The reseason of not effective is because their signal is in the bad condition, some of them can not use Quizziz properly, and they said that using Quizziz make the study more complex and complicated, maybe there are some reasons why Teaching reading comprehension using Quizziz doesn’t effective.